Selective inheritance of target genes from only one parent of sexually reproduced F1 progeny in Arabidopsis - Tao Zhang (Nature Portfolio, 2021)
Unlike insects and mice, CRISPR/Cas9-based gene drives have not been achieved in plants. Here, the authors demonstrate homozygous F1 Arabidopsis plants can be obtained through zygotic conversion using CRISPR/Cas9-mediated homology-directed repair.